Large-scale experiments on the behaviour of a generalised Oscillating Water Column under random waves. (December 2016) - Viviano, Antonino; Naty, Stefania; Foti, Enrico; Bruce, Tom; Allsop, William; Vicinanza, Diego
Abstract: This work investigates wave reflection and loading on a generalised Oscillating Water Column (OWC) wave energy converter by means of large scale (approximately 1:5–1:9) experiments in the Grosse Wellenkanal (GWK), in which variation of both still water depth and orifice (PTO) dimension are investigated under random waves. The model set-up, calibration methodology, reflection analyses and loadings acting on the OWC are reported. On the basis of wave reflection analysis, the optimum orifice is defined as that restriction which causes the smallest reflection coefficient and thus the greatest wave energy extraction. Pressures on the front wall, rear wall and chamber ceiling are measured. Maximum pressures on the vertical walls, and resulting integrated forces, are compared with available formulations for impulsive loading prediction, which showed significant underestimation for heaviest loading conditions. The present study demonstrates that a OWC structure can serve as a wave absorber for reducing wave reflection. Thus it can be integrated in vertical wall breakwaters, in place of other perforated low reflection alternatives. The possibility to convert air kinetic into electric energy, by means of a turbine, may give an additional benefit. Thus the installation of such kind of energy converters becomes interesting also in low energy seas. Highlights: An Oscillating Water Column wave energy converter has been studied. Unique, large scale physical model tests have been carried out and analyzed. The Oscillating Water Column has been demonstrated to function as a wave absorber reducing wave reflection. Loadings on the front face and on the rear, in chamber wall of the structure, have been measured and are compared with available formulations/information. Loadings on the chamber ceiling are presented and quantified for the first time.